Risk factors and outcomes for carbapenem-resistant Klebsiella pneumoniae bacteremia in onco-hematological patients - Jianling Liu; Haichen Wang; Ziyan Huang; Xiaoyan Tao; Jun Li; Yongmei Hu; Qingya Dou; Mingxiang Zou (Journal of Infection in Developing Countries)
Introduction: Carbapenem-resistant Klebsiella pneumoniae (KP) serves as a major threat to onco-hematological patients, resulting in great morbidity and mortality. The purpose of our study was to identify the risk factors for KP bloodstream infections (BSIs) and mortality in onco-hematological patients.